TEACHER READINESS IN IMPLEMENTING THE MERDEKA CURRICULUM: A STUDY ON BANJARMASIN PGRI HIGH SCHOOL - Arbayah, Siti; Adyatma, Sidharta; Hastuti, Karunia Puji; Angriani, Parida; Aristin, Nevy Farista (JURNAL SOCIUS, 2024)
This study is motivated by the implementation of the Merdeka Curriculum at all levels of education which requires teachers to understand the implementation of the Merdeka Curriculum. Based on this, the purpose of this study is to determine the readiness of PGRI High School teachers in implementing the Merdeka Curriculum in West Banjarmasin District. This research data is primary data in the form of direct observation results, and secondary data in the form of literature studies in the form of journals, and reports. The research sample consisted of 12 teaching teachers from the social science subject of PGRI High School in West Banjarmasin District who were registered as implementers of the Merdeka Curriculum. Data were collected by distributing questionnaires to 12 social science teaching teachers. Data analysis used descriptive statistics, namely tabulation percentages to analyse the level of teacher readiness for the implementation of the Merdeka curriculum at PGRI High Schools in West Banjarmasin District. The Merdeka curriculum is a policy issued by the Ministry of Education, Culture Research and Technology which aims to optimise learning with the previous curriculum. Teacher readiness in implementing the Merdeka curriculum varies regardless of the competencies possessed by the teacher. A teacher's competence is a set of mastery of abilities that must exist in order to realise performance which includes pedagogic competence, professional competence, personality competence, and social competence. The results showed that the readiness of teachers in implementing the Merdeka curriculum at PGRI High School in West Banjarmasin District was in the ready category, which was at 19.5%. The readiness of the teachers in implementing the Merdeka curriculum is by attending IHT trainings as well as seminars to improve the quality of a teacher.